Hepatocyte growth factor induces Mcl-1 in primary human hepatocytes and inhibits CD95-mediated apoptosis via Akt - Schulze-Bergkamen, Henning; Brenner, Dirk; Krueger, Andreas; Suess, Dorothee; Fas, Stefanie C.; Frey, Christian R.; Dax, Andreas; Zink, Dorothea; Büchler, Peter; Müller-Schilling, Martina; Krammer, Peter H. (Hepatology, 2004)
CD95 (APO-1/Fas)-mediated apoptosis of hepatocytes plays a central role in the pathophysiology of various human liver diseases. Hepatocyte growth factor (HGF) was shown to exert antiapoptotic functions in rodent hepatocytes. We previously showed that primary human hepatocytes (PHH) are a valuable tool for the investigation of apoptotic processes in liver cells. In this study, we analyzed the influence of HGF on CD95-mediated apoptosis of PHH and its molecular determinants. HGF significantly inhibited CD95-mediated apoptosis of PHH as well as cleavage of caspase-8 and poly (ADP-ribose)polymerase. HGF transcriptionally induced the expression of the anti-apoptotic Bcl-2 family member myeloid cell leukemia-1 (Mcl-1). In contrary, HGF did not alter the expression levels of Bcl-2 or Bcl-xL. HGF activated survival pathways such as the phosphatidylinositol-3 kinase (PI3K)/Akt pathway, the mitogen-activated protein kinase/extracellular signal-regulated kinase (ERK) kinase/ERK and the signal transducer and activator of transcription 3 (STAT3) pathway. Notably, HGF triggered serine727—but not tyrosine705—phosphorylation of STAT3. Pretreatment of PHH with the PI3K inhibitor LY294002 as well as adenoviral transduction of dominant negative Akt1 prevented HGF-mediated Mcl-1 induction and reversed the antiapoptotic effects of HGF. In conclusion, HGF confers survival of PHH by activation of the PI3K/Akt pathway. PI3K/Akt activation by HGF results in the induction of antiapoptotic proteins such as Mcl-1. Thus, application of HGF may be a therapeutic approach to prevent CD95-mediated hepatocellular damage in human liver diseases. (HEPATOLOGY 2004;39:645-654.)